On the mechanism of hydrogen activation by frustrated lewis pairs - Zeonjuk, Lei Liu; Vankova, Nina; Mavrandonakis, Andreas; Heine, Thomas; Roeschenthaler, Gerd-Volker; Eicher, Johannes (Chemistry - A European Journal, 2013)
We report herein a comprehensive theoretical study of the thermodynamics and kinetics of molecular hydrogen activation by frustrated Lewis pairs (FLPs). A series of intermolecularly combined boranes (Lewis acids) and phosphines (Lewis bases), with experimentally established different reactivities towards H2, have been subjected to DFT and (SCS-)MP2 calculations, and analyzed in terms of their structural properties, the energetics of association of the FLPs, and the kinetics of their interactions with H2 and hydrogenation to the ion-pair products. The analysis included the following steps: 1) assessment of the ability/inability of the Lewis species to preorganize into FLPs with an optimum arrangement of the acid and base sites for preconditioning the reaction with H2, 2) comprehension of the different thermodynamics of hydrogenation of the selected FLPs by comparing the Gibbs energies of the overall reactions, and 3) estimation of the mechanism of the activation of H2 by identifying the reaction steps and the associated kinetic barriers. The results of our studies correlate well with experimental findings and have clarified the reasons for the observed different reactivities of the investigated systems, ranging from reversible or nonreversible activation to no reaction with H2. The derived predictions could assist the future design of Lewis acid-base systems with desired properties and applicability as metal-free hydrogenation catalysts. Metal-free H2 activation: Computational studies clarify the reasons for the experimentally observed different abilities of a series of frustrated Lewis pairs (FLPs) to activate molecular hydrogen (see figure). © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: ab initio calculations; density functional theory; hydrogen activation; Lewis pairs; reaction mechanisms